KONDISI SOSIAL EKONOMI PETANI DI PROVINSI BALI SEBUAH ANALISIS DATA SEKUNDER BERDASARKAN HASIL SENSUS PERTANIAN 2003 - Sudibia, I Ketut (PIRAMIDA, 2012)
The objective of this study is to analyze social and economic condition of the farmers in Province of Bali. The main data is obtained from The Agricultural Census 2003, specifically ?The Survey of Farmers? Income 2004?. Data is analyzed using techniques of descriptive, qualitative, and comparative. Some findings of this study are (1) the shifting of young generation orientation from agricultural sector to non-agricultural sector in Denpasar city, Badung and Gianyar regencies; (2) the level of education of farmers are relatively low, even in several regencies like Buleleng, Bangli, Klungkung, and Karangasem there are over than 80 percent of them are low educated (primary school and under); (3) the average cultivated non-rice field is 0.3987 hectares with composition of 61.1 percent of farmers cultivating less than 0.50 hectares, on the other side, the average cultivated rice field is 0.1534 hectares with composition of 76,1 percent of farmers cultivating less than 0.50 hectares; (4) the contribution of non-agricultural sector to the household income of farmers tends to be high for farmers that cultivate land less than 0.50 hectares; and (5) the income levels of farmers in Province of Bali are relatively low, compared to the minimum standard of living or per capita income of Bali population in the same period. Furthermore, some suggestions emerge from this study are needs of (1) enhancement of farmers education through farmers training; (2) protection to the farmers in terms of production input and strategic commodities in order to decrease the impressions that agricultural sector is less protected; and (3) creation of balanced development between agricultural and non-agricultural sectors, so that both sectors are developed.
Keywords: the shifting of young generation orientation, low level of farmers? income, farmers? protection, and balance development